Designing a new pentagonal bipyramidal bridged dinuclear cadmium(II) complex as a bio-active compound: Synthesis, X-ray crystal structures, spectroscopic, DFT, and molecular docking studies - Qand, Alaa Salim; Al-Karawi, Ahmed Jasim M.; Abdallah, Abanoub Mosaad; Dege, Necmi; Hekim, Seda (Elsevier Science Inc, 2026)
A new bridged dinuclear cadmium(II) complex: [CdII2(L)2Cl4] (1) is synthesized and characterized through comprehensive spectroscopic and analytical investigations. Each Cd(II) center exhibits a seven-coordinate environment with a distorted pentagonal bipyramidal geometry. Density Functional Theory (DFT) calculations were performed at the B3LYP/LANL2DZ level to optimize the molecular geometry and to simulate the vibrational and electronic (UV-Vis) spectra. Frontier molecular orbital (HOMO-LUMO) analysis and global reactivity descriptors, including chemical hardness and softness, were evaluated to gain deeper insight into the electronic structure and chemical reactivity of both the free ligand and its cadmium complex. In addition, Molecular Electrostatic Potential (MEP) mapping was employed to identify electrophilic and nucleophilic regions and to explore intermolecular interactions that govern crystal packing. To investigate the structure-activity relationship, molecular docking studies were conducted to assess the binding modes and affinities of L and compound 1 toward the alpha-glucosidase enzyme. The docking results revealed favorable binding energies and stable interactions within the enzyme active site. These findings were further supported by in vitro biological evaluations. Enzyme inhibition and kinetic studies demonstrated that both compounds act as non-competitive alpha-glucosidase inhibitors, highlighting their potential as lead candidates for novel antidiabetic agents. Furthermore, the synthesized compounds exhibited notable antimicrobial activity against selected bacterial strains, with minimum inhibitory concentration (MIC) values ranging from 16 to 64 mu g/mL. Overall, the integration of experimental characterization, theoretical calculations, and biological investigations underscores the structural uniqueness and promising bioactivity of the newly synthesized cadmium(II) complex, paving the way for further pharmaceutical exploration.
Keywords: Seven-Coordinate Cadmium(Ii) Complex; Bridged Dinuclear Cadmium(Ii) Complex; Enzyme Inhibitors; Antimicrobial; Bio-Active Materials; Dft Calculations